Reviewing Hydrocephalus: Personal experience of a Neurosurgeon with Ventriculoperitoneal shunts treatment - Gautam, Vinod Kumar Singh; Singh, Ravinder; Khurana, Sarbjeet (International Journal of Medicine, 2014)
Background: Hydrocephalus is one of the most common neurologic sequelae following insult to the central nervous system. The treatment of hydrocephalus is very challenging. Ventriculoperitoneal shunt surgery is the commonest form of CSF diversion procedure for hydrocephalus. The objective of this study is to look critically at the efficacy of this procedure and compare the outcome with other studies involving different therapeutic options for treating hydrocephalus. Material & Methods: Fourty three patients of hydrocephalus who were operated for ventriculoperitoneal shunt placement were included in the study. Review of medical records including operative notes, imaging studies and clinic-radiological follow up of all the patients were reviewed and analyzed. Results: The common etiologies include post meningitic hydrocephalus, congenital hydrocephalus, NPH, posterior fossa tuberculomas, neurocysticercosis and posterior fossa tumor. Right sided ventriculoperitoneal shunt with medium pressure valve system was the commonest modality of treatment. None of the patients had any incidence of shunt infection. Conclusion: The results of this retrospective study show that ventriculoperitoneal shunting is effective in the management of adult patients with obstructive hydrocephalus. The overall incidence of shunt revision was comparable with previously reported studies in the literature. Keywords: Hydrocephalus, Ventriculoperitoneal Shunt.